Response Surface Modeling for Cutting Force and Power Consumption during Turning using Vegetable Oils - Ghuge, N.C.; Mahalle, A.M. (Journal of Engineering and Technology (JET), 2016)
Minimum quantity lubrication (MQL) is an impending technique to reduce the amount of cutting fluid and to improve the performance of the manufacturing process. Nowadays, researchers are trying to eliminate the harmful mineral- based cutting fluids. It is necessary to develop a low cost MQL system and to evaluate its performance using vegetable oil as cutting fluid in comparison with dry and flood cutting. To sustain the quality, to reduce the machining costs and to increase the production rate, selection of optimal cutting parameters as such is an important task. Response surface methodology is used to examine the experimental results. Numerical model for each cutting forces and power consumption is developed to show the relation between significant parameters such as cutting speed, depth of cut and feed rate. Analysis of variance test is performed to make sure the adequacy of the developed model. To find out the best combination of the cutting speed, feed and depth of cut for desired performance, multi-response optimization is carried out. Desirability value shows the feasibility of optimization for multiple responses. The results showed that all the developed models are accurate and adequate. MQL with vegetable oil performed better as compared to mineral-based oil.